(untitled) (Sains Humanika, 2021)
To deal with Industry 4.0, college students need to develop not only skills related to computers but also humans. Former Indonesian Minister of Research,Technology, and Higher Education had emphasized the urgency for this area. However, research articles that support the rationale of Human Literacy are still limited. Thus, this research was conducted to find the definition of Human Literacy and its aspects. Interviews were conducted to 41 students from 8 faculties at Soegijapranata Catholic University. This was followed by content analysis to interpret the meaning. We analyzed the compilation of the interview and looped the meaning of Human Literacy for college students into four main points, which are (1) humanizing humans, (2) technology literacy, (3) character formation, and (4) support from significant institutions. Additional quantitative data also showed the needs of discussion about Human Literacy for students. The result accentuates that learning of Human Literacy for future workers is an issue needs to be concerned by Higher Education Institutions.